P Pemanfaatan Arduino Uno sebagai Alat Ukur Offset Voltage pada Infra Red Detector type TO39 dengan pembanding alat ukur DMM - Gunawan Hadiyanto (Elkom : Jurnal Elektronika dan Komputer, 2021)
The infrared detector (or IR detector) is an optoelectronic component and represents the core element of gas analyzers, flame sensors, devices of spectral analysis, as well as non-contact temperature measurement. pyroelectric infrared detectors work with stabilization time in a wide operating temperature range (-55 ... 85) °C, capable of measuring the slightest amounts of infrared radiation (as little as a fraction of a nW) with wavelengths between 1 µm and > 25 µm. The difference of the good pyroelectric or No good (NG) devices shown by graph of voltage offset operating that can check by manual using Digital Multi Meter or semi auto by using microcontroller One of importance measuring of IRD sensors is Offset Voltage, stabilization of offset voltage indicate the sensor is stable with certain level value. Stabilization value measurement during measuring time means the average value not so much different with fluctuation value. 10 bit ADC on Atmega 328 that main microcontroller on Arduino Uno is capable to measure the Offset Voltage of IRD sensor and check the measurement values is within specification of IRD sensor.